Perception of Dissolved Food-Related Compounds by the Sea Urchin Paracentrotus lividus (Echinodermata: Echinoidea) - Luis, Orlando J.; Gago, João M. (Frontiers in Marine Science, 2021)
Echinoid feeding biology is well known but their sluggish responses to chemical stimuli have turned them into inadequately worked in the field of chemoreception. Echinoid responses to chemical stimulation had allowed, so far, only qualitative analyses based on tube-feet activity, directional, or masticatory movements, and artificial agarose foods. Besides stimulation through plumes of dissolved organic compounds and response analysis based on tube-feet activity, we propose another method to chemically stimulate echinoids that allows for fast and unambiguous responses and thus, quantitative analyses. Small squared pieces of absorbent semi-synthetic cleaning cloths, soaked with specific chemical compounds (simulacra), such as water insoluble lipid oils, were deposited singly or concurrently with a blank on the aboral hemisphere of each sea urchin, allowing choice and eventual transport down to the mouth by tube feet and spines of one or both cloths. The responsiveness of Paracentrotus lividus was clearly dependent on its nutritional state. Well-fed sea urchins (maize whole grains) rarely responded, while the ones fed with less caloric rations (Kombu seaweed) responded faster and objectively. Stimulating sea urchin P. lividus with 41 different food-related compounds, such as carbohydrates, proteins, peptides and amino acids, oils and fatty acids, and purified chemicals related with some human basic tastes, it was possible to evidence a clear ability of this echinoid species to positively discriminate proteins, starches, and a very few oils. Perceived as incitants/stimulants we have only found among proteins gliadin (from wheat gluten) but not casein (from bovine milk), among polysaccharides starch but not laminarin (from kelp) or glycogen (from mussels), and among lipids only the fatty acid linolenic acid. Among tissues, Kombu alga flesh and mussel flesh were readily perceived as both incitant/stimulant but not Kombu and mussel extracts. Therefore, the combined results reported here provide evidence for P. lividus as an omnivorous species rather than a strictly herbivorous marine species. However, the restricted group of food-related compounds perceived by this species as incitants or suppressants and as stimulants or deterrents was shown to be remarkably related to other vertebrates whose kinship was confirmed by the sequencing of the genome of another plant-eater sea urchin.